2005
DOI: 10.1603/0022-0493-98.3.884
|View full text |Cite
|
Sign up to set email alerts
|

Using Yellow Rocket as a Trap Crop for Diamondback Moth (Lepidoptera: Plutellidae)

Abstract: Yellow rocket, Barbarea vulgaris (R. Br.) variety arcuata, was evaluated as a trap crop for diamondback moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae), in cabbage, Brassica oleracea L. variety capitata, in 2003L. variety capitata, in and 2004L. variety capitata, in . In 2003, the numbers of P. xylostella larvae found in Þeld plots of cabbage alone were 5.2Ð11.3 times higher than those on cabbage plants in plots that included cabbage and several rows of yellow rocket. In an outdoor experiment in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 33 publications
(31 reference statements)
1
34
0
Order By: Relevance
“…To our knowledge, only two studies have attempted to measure even proxies for insect retention by trap crops (Borden & Greenwood 2000; Badenes‐Perez, Shelton & Nault 2005). Borden and Greenwood studied baited trees as trap plants for spruce and bark beetles and concluded that the baited trees’ higher retention potentially contributed to the trap crop’s commercial success.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only two studies have attempted to measure even proxies for insect retention by trap crops (Borden & Greenwood 2000; Badenes‐Perez, Shelton & Nault 2005). Borden and Greenwood studied baited trees as trap plants for spruce and bark beetles and concluded that the baited trees’ higher retention potentially contributed to the trap crop’s commercial success.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports on the high potential of trap cropping based on field studies using PSD plants include the diamondback moth Plutella xylostella whose infestations in cabbage fields were reduced using yellow rocket (Barbarea vulgaris) as a trap (Badenes-Perez et al 2005) and cotton bollworms Helicoverpa spp. whose infestations in cotton fields were reduced using field pea (Pisum sativum) in Australia (Grundy et al 2004) and grain sorghum (S. bicolor) in the USA (Tillman and Mullinix 2004).…”
Section: Pest Deterrence or Repellencementioning
confidence: 99%
“…Due to genetic variation for strong resistance to an oomycete plant pathogen (van Mölken et al, 2014a,b) and three agricultural pests, the diamondback moth, Plutella xylostella (Shinoda et al, 2002), the flea beetle Phyllotreta nemorum (Nielsen, 1997) and the cabbage moth, Mamestra brassicae (van Leur et al, 2008), B. vulgaris is also being investigated for useful genes for plant breeding (Augustin et al, 2012;Kuzina et al, 2009Kuzina et al, , 2011Wei et al, 2013) or direct agronomic use as 'deadend' trap crop (Badenes-Pérez et al, 2005. Traditional taxonomy of the species is controversial, possibly because the morphological characters available to classical taxonomists were not sufficiently informative (Agerbirk et al, 2003).…”
Section: Introductionmentioning
confidence: 99%